PENDIDIKAN AGAMA DAN UPAYA PENGUATAN KERUKUNAN UMAT BERAGAMA - Suriyanti, Intan (JURNAL IMPARTA, 2025)
Religious harmony is an important foundation for social stability and national integration in Indonesia, which is known as a multicultural and multireligious country. This article aims to examine the strategic role of education in building inter-religious harmony through a literature study approach. Using a descriptive qualitative method, this study analyses various academic sources published in the last 10 years that discuss tolerance education, religious moderation, and multicultural education. The results of the study show that formal and non-formal education play a significant role in instilling the values of tolerance, mutual respect, and interfaith dialogue. The practice of interfaith education in elementary schools has proven to be effective in forming an inclusive character from an early age. In the context of Christian religious education, the values of love, forgiveness, and respect for human dignity are the basis of religious moderation that is relevant to a pluralistic society. However, the implementation of interfaith education still faces challenges such as ideological resistance, limited teacher training, and a curriculum that is not fully multicultural. This article recommends the development of an interfaith curriculum based on universal values, teacher training in a multicultural approach, and the integration of interfaith activities in the educational environment. Education that is designed in a contextual and reflective manner can be a transformative instrument in building a peaceful, equitable, and inclusive society.